2020
DOI: 10.1016/j.crphys.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Increased fatty acid oxidation enzyme activity in the hearts of mice fed a high fat diet does not correlate with improved cardiac contractile function

Abstract: Changes in the acetylation status of mitochondrial proteins have been linked to the development of metabolic dysfunction in a number of tissues. Increased lysine acetylation has been reported in the hearts of obese mice, and is associated with changes in fuel metabolism, redox status, and mitochondrial oxidative phosphorylation. In this study, we examined whether diet-induced changes in the acetylation of mitochondrial acyl-CoA dehydrogenases affected fatty acid oxidation enzyme activity and contractile functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Previous work from our group and others has demonstrated that increased mitochondrial protein acetylation in the heart is linked with increased rates of fatty acid oxidation ex vivo and in vitro (Alrob et al, 2014 ; Fukushima et al, 2016 ; Thapa et al, 2017 ). However, the functional consequence of this change is unclear, as increased fatty acid oxidation activities in hyperacetylated hearts did not directly lead to increased contractility under ex vivo conditions (Thapa, Manning, Mushala, et al, 2020 ). Results from the current study are instead in agreement with previous work showing that PDH acetylation is linked to a decrease in its activity in the heart in vivo and ex vivo (Mori et al, 2013 ; Thapa et al, 2019 ), and that GCN5L1 overexpression leads to elevated PDH acetylation in vivo and in vitro (Thapa et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our group and others has demonstrated that increased mitochondrial protein acetylation in the heart is linked with increased rates of fatty acid oxidation ex vivo and in vitro (Alrob et al, 2014 ; Fukushima et al, 2016 ; Thapa et al, 2017 ). However, the functional consequence of this change is unclear, as increased fatty acid oxidation activities in hyperacetylated hearts did not directly lead to increased contractility under ex vivo conditions (Thapa, Manning, Mushala, et al, 2020 ). Results from the current study are instead in agreement with previous work showing that PDH acetylation is linked to a decrease in its activity in the heart in vivo and ex vivo (Mori et al, 2013 ; Thapa et al, 2019 ), and that GCN5L1 overexpression leads to elevated PDH acetylation in vivo and in vitro (Thapa et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our group and others has demonstrated that increased mitochondrial protein acetylation in the heart is linked with increased rates of fatty acid oxidation ex vivo and in vitro [7,15,16] . However, the functional consequence of this change is unclear, as increased fatty acid oxidation activities from hyperacetylated hearts did not lead to increased contractility when measured ex vivo [17] . Results from the current study are instead in agreement with previous work showing that PDH acetylation is linked to a decrease in its activity in the heart in vivo and ex vivo [8,18] , and that GCN5L1 overexpression leads to elevated PDH acetylation and in vitro [8] .…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling research indicating that GCN5L1 plays a critical role in regulating protein acetylation in the heart during maturation [ 18 ]. Further studies have confirmed that GCN5L1 plays a role in regulating energy substrate utilization and maintaining mitochondrial homeostasis in the adult heart [ 14 , 19 21 ]. However, whether GCN5L1 mediates MPC acetylation and leads to CF exploitation of glycolysis is unclear.…”
Section: Introductionmentioning
confidence: 99%